Educação médica no armário: vivências e formação de estudantes LGBTQIA+ - Brito, Luana Camargo (2021)
Based on several reports of offensive behaviors directed at the LGBTQIA + population during the medical course and a lack of information on sexual and gender diversity in medical graduation, the present text aims to understand how the LGBTQIA + students experience in the medical course and medical training for issues of sexual and gender diversity. This is a descriptive and exploratory research with a qualitative approach. Semi-structured interviews were conducted with 12 LGBTQIA + students from the medical course at an institution in the Brazilian Midwest. From the discourse analysis, the following interpretive repertoires were identified: 1) The closet for the family: life before university, in which reports of the definitions of sexual identities and the exit or maintenance in the closet in front of his family are evidenced; 2) University life in the closet: concealment and injury, about the experiences of LGBTQIA+ university students in the medical course and their interaction with colleagues and professors; and 3) Curriculum in the closet, presenting questions related to the care of the LGBTQIA + population and what is taught during graduation. The discussion about the LGBTQIA + in medical institutions is important because it fosters changes in medical teaching, considering the social function of the course and recognizing students and patients in all its uniqueness.